(3fRgI GdCMHGH heYGTQI Phi GdCdHGHs - (3CHh fUQ GdSehCd Hf jMji Hf YHGS GdeZQHj GdGSQGFjdj,J (B570 (3g` s ((3eMeO Hf SaQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd QMeJg ddePfHjf edGPkG hHYO abO CLeYJ Ydi EfTGA cJGH GdHGH GdChd ai YdGeGJ ef jbWYg Yf GdHGg s
(3BNQgG (B:s
(3hehGYX LdGjI ddbdhH GdUOjI hdG efacI Yf fUjMI fGaYI Je GdcJGH HMeO Gddg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdMOjK h GdeUWdMs